Submaximal Exercise Testing in Cardiovascular Rehabilitation Settings (BEST Study) - Reed, Jennifer L.; Cotie, Lisa M.; Cole, Christie A.; Harris, Jennifer; Moran, Bruce; Scott, Kyle; Terada, Tasuku; Buckley, John P.; Pipe, Andrew L. (Frontiers in Physiology, 2020)
Background: This study compared changes in actual versus predicted peak aerobic power (V̇O2peak) following cardiovascular rehabilitation (CR). Maximal cardiopulmonary exercise testing (CPET) results were compared to three submaximal estimation methods (a modified Bruce treadmill, Astrand-Ryhming cycle ergometer, and Chester step tests) and the Duke Activity Status Index (DASI). Methods: Adults with cardiovascular disease who completed a 12-week CR program were assessed at baseline and 12 weeks follow-up. CPET, the DASI and 3 subsequent submaximal exercise tests were performed in a random order. Results: Of the 50 adults (age: 57±11 years) who participated, 46 completed the 12-week CR program and exercise tests. At baseline 69%, 68% and 38% of the treadmill, step and cycle tests were successfully completed, respectively. At follow-up 67%, 80% and 46% of the treadmill, step and cycle tests were successfully completed, respectively. No severe adverse events occurred. Significant improvements in V̇O2peak were observed with CPET (3.6±5.5 mL.kg-1.min-1, p<0.001) and the DASI (2.3±4.2 mL.kg-1.min-1, p<0.001). Bland-Altman plots of the change in V̇O2peak between CPET and the four V̇O2peak estimation methods revealed the following: a proportional bias and heteroscedastic 95% limits of agreement (95% LoA) for the submaximal treadmill test, and for the cycle test, step test and DASI, mean bias’ and 95% LoA of 1.0 mL.kg-1.min-1 (21.3, -19.3), 1.4 mL.kg-1.min-1 (15.0, -12.3) and 1.0 mL.kg-1.min-1 (13.8, -11.8), respectively. Conclusion: Given the greater number of successful tests, no serious adverse events and acceptable mean bias, the step test appears to be a valid and safe method for assessing mean changes in V̇O2peak among patients in CR. The DASI also appears to be a valid and practical questionnaire. Wide limits of agreement, however, limit their use to predict individual-level changes.